2018
DOI: 10.4103/apjon.apjon_65_17
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Relationship between Religiosity and Quality of Life in Patients with Breast Cancer: A Study in Iranian Muslims

Abstract: Objective:This study aimed to assess the relationship between religiosity and quality of life (QoL) in patients with breast cancer in a Muslim population.Methods:This descriptive-correlational study was conducted in 84 Muslim patients with breast cancer who were admitted to Ahvaz Shafa Hospital, Iran, during 2015. QoL and religiosity were measured with the Short Form-36 questionnaire and Muslim Religiosity questionnaire based on the Glock and Stark model, respectively. Data were analyzed using a software progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…An investigation conducted in Croatia with cancer patients showed that depression was less prevalent in the high-religiosity group of breast cancer patients, and religiosity is a more easily accessible coping resource in situations of limited predictability (Aukst-Margetiç et al, 2005). The same relationship between religiosity and a better quality of life among cancer patients was found in a study with Iranian Muslims (Zargani et al, 2018) and in Saudi Arabia (Al Eid et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…An investigation conducted in Croatia with cancer patients showed that depression was less prevalent in the high-religiosity group of breast cancer patients, and religiosity is a more easily accessible coping resource in situations of limited predictability (Aukst-Margetiç et al, 2005). The same relationship between religiosity and a better quality of life among cancer patients was found in a study with Iranian Muslims (Zargani et al, 2018) and in Saudi Arabia (Al Eid et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, Farwah's research (2013) showed that religiosity and income affect Islamic well-being. Saleem and Saleem (2017) and Zargani et al (2018) also stressed that religiosity has a significant effect on the Muslim's well-being. Achour et al (2015) pointed out that beliefs, worship, and prayer have a positive association with well-being.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies conducted in cross-sectional design and only two studies employed prospective design [32]. Religiosity was measure using Santa clara strength of religious faith questionnaire (SCSORF) instrument in two studies [31], [33], two studies used the Duke Religious Index, one study used the brief measure of religious coping [34], two studies used religious coping (RCOPE) [21], [22], one study used systems of belief inventory-15 revised [24], [35] used Serajzadeh's muslim religiosity questiossnnaire. Quality of life was measured using a functional assessment of cancer therapy-general (FACT-G) [21], [24], [33], two studies used short form-36 health survey [35], and other studies used quality of life index (QLI), European organization for the research and treatment of cancer (EORTC) Quality of life questionnaire core 30, and international breast cancer study group quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…All studies investigated the relation between religiosity and quality of life. Most of studies reported positive correlation and direct effect between religiosity and quality of life [20], [21], [24], [31], [35]. Two studies reported no association between religiosity and quality of life [33], [34].…”
mentioning
confidence: 99%